IDENTIFIKASI SUBSEKTOR UNGGULAN PERIKANAN DI KABUPATEN ROKAN HILIR PROVINSI RIAU - M Eka Ramadhan; Sisca Vaulina (UIR Press, 2023)
Rokan Hilir Regency (Rohil) is an area with the highest fisheries production in Riau Province. This research aims to (1) determine the basic and non-basic subsectors in the fisheries subsector, (2) analyze the growth of fisheries subsectors towards GRDP in the economic development of Rohil Regency, and (3) understand the growth pattern in fisheries subsectors in Rohil Regency. The method used is a literature study, secondary data in the form of the time series 2017–2021, and analysis tools, namely Location Quotient (LQ), Shift Share, and Klassen Typology. The results showed that (1) sector basic in the economy of Rohil Regency was the marine capture fisheries subsector and the marine aquaculture subsector, while the non-basic subsector was the inland capture fisheries subsector, pond aquaculture, cage aquaculture, floating net aquaculture in inland waters, freshwater gillnet fisheries, and floating net aquaculture in the sea. (2) Subsectors experiencing proportional growth (PP) are the inland capture fisheries subsector and the pond aquaculture subsector. Subsectors experiencing regional growth (PW) with competitiveness were the inland capture fisheries subsector and the pond aquaculture subsector. (3) The position of the fisheries consisted of Quadrant I (aquaculture at sea and marine capture fisheries), Quadrant II (no subsector entering Quadrant II), Quadrant III (inland capture fisheries, freshwater floating net aquaculture), and Quadrant IV (pond aquaculture, cage aquaculture, freshwater floating net aquaculture, and floating net aquaculture in the sea).